Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1177/0954409713508109
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of a bird impact on a composite aerodynamic brake wing of a high-speed train

Abstract: Experimental bird strike tests were conducted in which a 2.6-kg dead chicken was projected at a speed of 500 km/h to hit a raised aerodynamic brake wing. The brake wing was fabricated with a sandwich of composite material as its skin and polymethacrylimide foam as its core. Pre-test numerical analyses of bird strikes were performed using the LS-Dyna solver code, an Arbitrary Lagrangian Eulerian model of the bird, and a Lagrangian model of the brake wing. The numerical and experimental results were well correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 15 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…It is found that the effect of plate braking in the high-speed stage is obvious [3][4][5] . By means of simulations and full-scale tests, some researchers found that the plate shape has little effect on the braking effect [6] , however, it has an impact on the lateral aerodynamic performance of the train, and it may be a better choice to keep the plate shape consistent with the top surface of the train [7] . Considering the mechanical structure and ow eld changes comprehensively, it is determined that the reasonable plate opening angle is about 75 degrees [8,9] , the effect of arranging the plates in series on the train roof is better than is better than that of arranging a single plate with equal area [10] ; it is also found that car-connection part is an ideal location for arranging the plates, effect of placing a single large plate downstream of the car-connection is better than that of setting a single large plate upstream of the car-connection, and two small plates respectively upstream and downstream of the car-connection [12] .…”
Section: Introductionmentioning
confidence: 99%
“…It is found that the effect of plate braking in the high-speed stage is obvious [3][4][5] . By means of simulations and full-scale tests, some researchers found that the plate shape has little effect on the braking effect [6] , however, it has an impact on the lateral aerodynamic performance of the train, and it may be a better choice to keep the plate shape consistent with the top surface of the train [7] . Considering the mechanical structure and ow eld changes comprehensively, it is determined that the reasonable plate opening angle is about 75 degrees [8,9] , the effect of arranging the plates in series on the train roof is better than is better than that of arranging a single plate with equal area [10] ; it is also found that car-connection part is an ideal location for arranging the plates, effect of placing a single large plate downstream of the car-connection is better than that of setting a single large plate upstream of the car-connection, and two small plates respectively upstream and downstream of the car-connection [12] .…”
Section: Introductionmentioning
confidence: 99%